(untitled) (The Educator Journal, 2025)
With an emphasis on a case study carried out at a community school, this research piece examines the difficulties encountered by slow arithmetic learners. Students with IQs below average are known as slow learners, and they frequently face scholastic challenges as a result of a confluence of emotional, environmental, and psychological variables. Using a qualitative research methodology, this study examines secondary source data and case studies to pinpoint the main reasons why students struggle with mathematics and assess potential remedial measures. A review of previous research, case studies, teacher, parent, and peer group interviews, as well as firsthand observations of classroom dynamics, are all part of the process. Results show that constant evaluation, positive reinforcement, and specialized teaching methods greatly help slow learners. Addressing sluggish learning also requires teacher preparation and parental involvement. To meet a range of learning requirements, recommendations include integrating technology-based resources, creating supportive learning environments, and providing tailored training. This study adds to the current conversation about inclusive education by emphasizing workable ways to help delayed learners succeed academically.